Dopamine receptor polymorphism modulates the relation between antenatal maternal anxiety and fetal movement. Issue 8 (19th May 2016) - Kaitz, Marsha; Mankuta, David; Rokem, Ann Marie; Faraone, Stephen
Abstract: We determined whether the combination of fetal genotype (dopamine D4 receptor; DRD4) and mothers' anxiety during pregnancy is associated with fetal behavior. Two hundred and six pregnant women underwent an ultrasound exam. Fetal movement measures (Movement Frequency, Total Activity, Movement Duration, and Longest Quiet Time) were derived from off‐line coding. A moderating role of the DRD4‐III polymorphism was found: Results indicate that higher levels of antenatal maternal anxiety symptoms were associated with more frequent fetal movements among fetuses carrying a 7R allele, but not among fetuses carrying shorter alleles. Total Activity did not show full moderation by DRD4, though the measure was correlated with maternal anxiety among fetuses in the Anxious Group with a 7R allele; not among fetuses without both factors. The findings provide the first evidence of a GXE interaction in association with fetal behavior. Results also demonstrate that some individuals are inherently more susceptible to uterine environmental influences than are others.